PENERAPAN MODEL PEMBELAJARAN RECIPROCAL LEARNING PADA MATERI PEMANASAN GLOBAL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Ramadhani, Reni; Azizahwati, Azizahwati; Rahmad, M. (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2024)
This research aims to describe students' problem solving abilities on global warming material through the reciprocal learning model and to determine the differences in students' problem solving abilities through the application of the reciprocal learning model and conventional learning models on global warming material. The research method used is a quasi experiment with a posttest-only control design. With data collection techniques in the form of a posttest. The sampling technique in this research used randomization. The sample in this study included classes VII D and VII E. The results of descriptive analysis in the experimental class obtained a problem solving ability score of 70.6 in the good category. Meanwhile, the control class obtained a score of 62.4, which is in the sufficient category. The hypothesis test result was obtained at 0.002, which means it is smaller than 0.05. There are differences in the problem solving abilities of students who apply the reciprocal learning model and apply conventional learning to global warming material at MTS Al-Qasimiyah Sorek Satu.